Human Resource Outsourcing: Issues and Challenges - Kodwani, Amitabh Deo (Journal of Nepalese Business Studies, 2008)
Business Process Outsourcing has become new mantra in the corporate business world. Modern as well as traditional organizations are now trimming down their employees from their payroll, and thus Human Resource Outsourcing (HRO) is slowly becoming the new buzzword. In order to utilize the true worth of the employees to its fullest, one must outsource the non-core activities of the organization. The awareness of this has already been realised by the organizations. Outsourcing has no longer the privilege of only huge multinational organizations. Even the public sector and government undertakings as well medium size or start-up companies are also in the race of outsourcing their many HR related activities. This paper examines the motives that are encouraging organizations to go for outsourcing HR, drawing the essence from extensive exploratory study of secondary literature. This paper presents an architectural framework to understand issues and challenges of HR HRO and to suggest what organizations should do to taste success from HRO. The Journal of Nepalese Business Studies Vol. IV, No. 1 (2007) pp. 38-46